Mindfulness in Marriage and Mindfulness in Parenting as Predictors of Social Skills in Early Childhood* - Karaagac, Zahide Gul; Deniz, M. Engin (CUKUROVA UNIV, 2023)
skills in early childhood, mindfulness in parenting, and mindfulness in marriage. The research was conducted based on the correlational survey model. The participants are 279 parents with children aged 3-7 years. The instruments that used for data collection were the Preschool and Kindergarten Behavior Scale (PKBS-2), Mindfulness in Marriage Scale (MMS), Mindfulness in Parenting Questionnaire (MPQ) and Personal Information Form. Independent samples t-test, correlation analysis, and multiple linear regression analysis were used to analyze the data. The results show that mindfulness in marriage and mindfulness in parenting have a positive and significant relationship with social skills in early childhood. According to the results of the regression analysis, mindfulness in marriage and mindfulness in parenting are significant predictors of children's social skills. The regression model has explained 27% of social skills. The research findings were discussed in light of the literature.
Keywords: Early Childhood; Mindfulness in Marriage; Mindfulness in Parenting; Social Skills; PRESCHOOL-CHILDREN; MARITAL RELATIONS; EMOTIONAL SECURITY; GENDER-DIFFERENCES; PEER RELATIONSHIPS; BEHAVIOR PROBLEMS; MEDIATING ROLE; CONFLICT; FAMILIES; SOCIALIZATION; Education & Educational Research